2000
DOI: 10.1603/0022-0493-93.6.1638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Insecticides on the Natural Enemies <I>Coleomegilla maculata</I> and <I>Hippodamia convergens</I> (Coleoptera: Coccinellidae), <I>Geocoris punctipes</I> (Hemiptera: Lygaeidae), and <I>Bracon mellitor, Cardiochiles nigriceps,</I> and <I>Cotesia marginiventris</I> (Hymenoptera: Braconidae) in Cotton

Abstract: We evaluated the toxicity of three insecticides (lambda cyhalothrin, spinosad, and S-1812) to the natural enemies Bracon mellitor Say, Cardiochiles nigriceps Viereck, Coleomegilla maculata De Geer, Cotesia marginiventris (Cresson), Geocoris punctipes (Say), and Hippodamia convergens Guérin-Méneville, in topical, residual, and field assays. Lambda cyhalothrin exhibited the greatest toxicity to the natural enemies. In topical toxicity tests, lambda cyhalothrin adversely affected each natural enemy species studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 7 publications
2
65
0
Order By: Relevance
“…Given its voracity toward these pests, C. undecimpunctata offers interesting potential as a control agent in the context of Integrated Pest Management (IPM) (ElHag 1992;Zaki et al 1999;Moura et al 2006;Cabral et al 2006Cabral et al , 2008. The success of IPM programs depends, in part, on the optimal use of selective insecticides that are less harmful to natural enemies (Tillman and Mulrooney 2000;Stark et al 2007), which requires knowledge of their side-effects on the biological and behavioural traits of these organisms (Tillman and Mulrooney 2000;Sechser et al 2003;Youn et al 2003;Liu and Stansly 2004;Bozski 2006;Desneux et al 2007;Stark et al 2007). Some studies have been done to assess the susceptibility of C. undecimpunctata to different insecticides but all, in some way, adversely affected this species (Salman and Abd-el-Raof 1979;Lowery and Isman 1995;Schroeder et al 1996;Omar et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Given its voracity toward these pests, C. undecimpunctata offers interesting potential as a control agent in the context of Integrated Pest Management (IPM) (ElHag 1992;Zaki et al 1999;Moura et al 2006;Cabral et al 2006Cabral et al , 2008. The success of IPM programs depends, in part, on the optimal use of selective insecticides that are less harmful to natural enemies (Tillman and Mulrooney 2000;Stark et al 2007), which requires knowledge of their side-effects on the biological and behavioural traits of these organisms (Tillman and Mulrooney 2000;Sechser et al 2003;Youn et al 2003;Liu and Stansly 2004;Bozski 2006;Desneux et al 2007;Stark et al 2007). Some studies have been done to assess the susceptibility of C. undecimpunctata to different insecticides but all, in some way, adversely affected this species (Salman and Abd-el-Raof 1979;Lowery and Isman 1995;Schroeder et al 1996;Omar et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because of poisoning risks, the use of selective products such as pyrethroids has been emphasized in this agroecosystem (Tillman & Mulrooney, 2000). Smagghe & Degheele (1995) studying the effects of RH 5849 and RH 5992 (tebufenozide) on P. nigrispinus, concluded that their nymphs did not show sensitivity to oral treatment (feeding on treated prey) or topical exposure.…”
Section: Introductionmentioning
confidence: 99%
“…That broad-spectrum pyrethroids are generally toxic to beneÞcial insects has been well documented by previous research (Tillman 1995;Ruberson and Tillman 1999;Tillman and Mulrooney 2000;Galvan et al 2005a,b). We found the pyrethroid lambda-cyhalothrin to be highly toxic to both C. maculata and D. insulare.…”
Section: Discussionmentioning
confidence: 66%